Native and Non-native Speeches in the 4th ELTIC Conference: Genre Analysis - Sudar Sudar (Soegijapranata Catholic University, 2020)
This study aims to investigate the production of speeches by native and non-native Keynote Speakers in the 4th ELTIC Conference. The speeches spoken by native and non-native speakers are investigated from a genre analysis. Particularly, it is from a rhetoric and linguistics perspective. The writer uses descriptive qualitative research. It is stated that speeches spoken by native and non-native have different rhetoric and linguistics styles when they were delivering their speeches in the conference. The native speaker delivering the speech is fully expressive and used linguistics styles based on the context. While the non-native delivers the speech formally and refers to references that were used. It meant that a native speaker uses rhetoric and linguistics styles naturally, while non-native speaker in delivering the speeches is still interfered by the first language styles.